The Influence of Self-Confidence And Creativity On Self-Actualization Of Arts UKM Members, Bhayangkara University, Jakarta Raya - Dzaki Fauzan (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Aims to explore the impact of self-confidence and creativity on the self-actualization of members in the Art Student Organization at Bhayangkara University Jakarta Raya. The study utilizes primary data collected through questionnaires and secondary data obtained from books and journals, specifically focusing on previous research findings. A total of 75 respondents participated in the study, and the data were analyzed using SPSS version 27. The results reveal a positive influence of both self-confidence and creativity on the self-actualization of the members. Notably, creativity emerged as the dominant factor, as indicated by a higher multiple linear regression coefficient compared to self-confidence and self-actualization.